The Development of Microhistorical Databases in Norway. A Historiography - Gunnar Thorvaldsen; Lars Holden (Historical Life Course Studies)
Norwegian work on microdata started out with the full count 1801 census and census and vital records from around the capital. Today, most census and ministerial records from 1801 until the mid-20th century have been scanned, transcriptions are being completed, much is encoded and made available via the websites of the Digital National Archives and UiT The Arctic University of Norway. This article complements a previous publication on empirical results from historical microdata. It is primarily organized by technical issues: digitization of source materials, encoding and standardization, building of the Historical Population Register for the period since 1800, record linkage and source criticism as well as GIS. Presently, partner institutions are building the Historical Population Register with prolonged support from the Norwegian Research Council. This will contain longitudinal records of the nine million persons who lived in Norway since 1800. The register increasingly makes it possible to follow the entire population. Unique personal IDs with corresponding URLs to the person page providing links to many sources introduce a new level of historical documentation. Cross-sectional and vital records are being interlinked with automatic and manual record linkage software. Longitudinal data is available for searching as timelines and in Intermediate Data Structure format from UiT The Arctic University and for searching at Histreg.no, which also caters for manual editing. We are well on the way to creating a database that can fill the void in the two centuries before the Central Population Register starts in 1964.